Pengembangan Media Pembelajaran Augmented Reality (AR) Berbasis Assemblr Edu Pada Pembelajaran IPAS Kelas V di SDN 1 Sepit - Husna, Asmaul; Alwi, Mijahamuddin; Fadilah, Dina (Program Studi Pendidikan Masyarakat, 2026)
Abstract: This study aims to develop Augmented Reality (AR) learning media based on assemblr edu in science learning for grade V at SDN 1 Sepit. This study is a type of Research and Development (R&D) research using the ADDIE development model which consists of 5 stages, namely: 1) Analysis, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. This research was conducted on all grade V students of SDN 1 Sepit, with a total of 30 students. The data collection techniques used in this study were in the form of expert team validation questionnaires and student response questionnaires on assemblr edu-based AR learning media which were analyzed using descriptive analysis techniques using a five-point scale for expert team validation and a four-point scale for student response questionnaires. The results of this study indicate that the validation of material experts is in the